Jaka Tarub's Artistic Costume Adapted to Metalu's 7 Wonders Webtoon - Dendy Kanaya Rai; Salsa Solli Nafsika (Universitas Pendidikan Indonesia, 2021)
This study discusses Jaka Tarub's costume adaptation of the 7 wonders webtoon. Costumes are the most important part of the artistic order to support the course of a show. In the production process of a work, costumes and makeup also become an important unit in building a visualization. And even then, the adaptation process when creating a work, namely the adaptation of Jaka Tarub's costume from Webtoon 7 wonders. The methodology that the researcher uses is a research base design, with steps of concept idea, implementation and evaluation. This research has succeeded in creating an adaptation of the visualization of the costume artistic arrangement that is in accordance with the image of the character in the 7 wonders webtoon story. This research can be a reference for artistic stylists of film costumes in exploring the richness of Indonesian localities to be adapted to global films.Keywords — Artistics, Costumes, Adaptations, Webtoon